Performance analysis of massive MIMO uplink with channel aging in high-speed mobile scenario - Lihua YANG; Yan LIANG (Dianxin kexue)
Achievable sum rate was investigated for the massive multiple input multiple output (MIMO) uplink system with channel aging in the high-speed mobile scenario,and the effect of both channel aging and the Ricean factor on the power scaling law was characterized.Theoretical analysis and simulation results show that the transmit power of each user is scaled down by 1/M for the time varying Rican fading channel indicating that the Ricean factor affects the power scaling law and sum rate,and achievable channel aging only leads to a reduction of the sum rate.Moreover,the effect of channel aging on the sum rate can be ignored compared with that of the Ricean factor in the time varying Ricean fading channel.